2017
DOI: 10.1021/acsami.7b06140
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrospray Printing of Gradient Refractive Index Chalcogenide Glass Films

Abstract: A spatially varying effective refractive index gradient using chalcogenide glass layers is printed on a silicon wafer using an optimized electrospray (ES) deposition process. Using solution-derived glass precursors, IR-transparent GeSbS and AsS glass films of programmed thickness are fabricated to yield a bilayer structure, resulting in an effective gradient refractive index (GRIN) film. Optical and compositional analysis tools confirm the optical and physical nature of the gradient in the resulting high-optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…88 Figure 8(b) shows the gradient film deposition profile of a bilayer of GeSbS and AsS glasses (on Si), and the variation in effective index, n eff , calculated based on the layer thickness and parent glass refractive indices, as deposited on a SiN resonator array. 56 Such deposition requires an electrically conductive substrate (i.e., Si), but is amenable to plano and other shaped substrates. In addition, the magnitude of the resulting index gradient is only defined by the film thickness and the excursion (Δn) between the candidate glasses used.…”
Section: Three-dimensional Printing Of Solution-derived Chg Glassesmentioning
confidence: 99%
“…88 Figure 8(b) shows the gradient film deposition profile of a bilayer of GeSbS and AsS glasses (on Si), and the variation in effective index, n eff , calculated based on the layer thickness and parent glass refractive indices, as deposited on a SiN resonator array. 56 Such deposition requires an electrically conductive substrate (i.e., Si), but is amenable to plano and other shaped substrates. In addition, the magnitude of the resulting index gradient is only defined by the film thickness and the excursion (Δn) between the candidate glasses used.…”
Section: Three-dimensional Printing Of Solution-derived Chg Glassesmentioning
confidence: 99%
“…To attain z-averages from the model for comparison with experiments, the average cluster size was calculated from eqn (15) and used to generate a normal distribution of sizes with the standard deviation observed in cryo-TEM. The z-averages were then calculated using eqn (1).…”
Section: As 2 S 3 + 6c 3 H 7 Nh 2 / (C 3 H 7 Nh 3 ) 3 Ass 3 + (C 3 H mentioning
confidence: 99%
“…12 The glasses dissolve in organic solvents and can then be doped, spin coated, or even inkjet printed with relative ease. [12][13][14][15] Previous research has shown numerous successful applications, including molded mid-IR waveguides, drop-cast photonic crystals, and optical bers with a nonlinearity-enhancing ChG coating. [16][17][18][19] The pioneering work on ChG solutions was done by Chern et al using As 2 S 3 in n-propylamine and n-butylamine as test systems.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray deposition has been shown to produce large index gradients (Δn ¼ 0.4) in thin films and shows promise for imaging optics. 25 Ink-jet printing is used commercially at Voxtel Inc. for GRIN optics, primarily in the visible, but can be extended to the IR using suitable inks. 26 Thermal poling has been used to create GRIN profiles with small gradients (Δn ¼ 0.05) suitable for microlens arrays.…”
Section: Introductionmentioning
confidence: 99%